Financial Bootstrapping Strategies in an Indonesian Edutech Startup: Transitioning from Non-Profit to Profit Orientation - Syauqi Amani; Sutrisno; Zaenal Arifin (International Journal of Economics, Business and Innovation Research, 2026)
This study Analyses the business performance and financial structure dynamics of Neuversity, an Edutech entity in Yogyakarta, Indonesia, during its strategic transition from a non-profit foundation (Yayasan) to a profit-oriented corporation (PT). The research evaluates the effectiveness of financial bootstrapping strategies in maintaining sustainability after the cessation of external grant funding. Method: Using a descriptive quantitative approach with a case study method, this research nalyses financial data from the third quarter (Q3) of 2025. The study focuses on Working Capital Management and Spontaneous Financing ratios. Results: The findings indicate that the company successfully pivoted to a B2B model. However, regarding Working Capital Management, the company faces liquidity constraints despite high profits, evidenced by a low Collection Rate of 44.5%. Conversely, the Financial Bootstrapping strategy proved effective, evidenced by an 18.1% ratio of spontaneous financing to total assets and a 56.6% cost reduction during low-revenue periods. Conclusion: While financial bootstrapping successfully secured operational sustainability without interest-bearing debt, long-term stability requires stricter liquidity discipline through better Working Capital Management.